Organizational Structure, Work Process, and Proposal Making in Administrative Bureaucracies - Aiken, Michaël; Bacharach, Samuel B.; French, J. Lawrence (Academy of Management Journal, 1980)
This paper examines the effect of organizational structures and processes on the reported proposals of innovation by middle and lower echelon officials in 44 Belgian bureaucracies. Technical and administrative innovations were examined. It was found that the determinants of proposal making differ, depending on the actor's level in the organization.